Unidentified bodies in the Mexican context - Fortuna, Maria; Corrales, Laura; Robinson, Alan; Enríguez Farias, Roxana; Márquez-Grant, Nicholas (University of Florida Press, 2022)
The discovery of clandestine graves has become a recurring fact during the last ten years in Mexico, estimating that there could be more than 2000 scattered throughout the country (Guillen et al., 2018). Less well known, reported and attended to are the mass graves, located in municipal or state census, which house bodies of unidentified people and of which there is no official census. It is estimated that there are some 26,000 unidentified bodies (SEGOB, 2019a) and annually, in Mexico City alone, almost 500 are destined for the cemetery mass grave. Comprehensive projects in forensic science are required to mitigate the high percentage of unidentified bodies that coordinate the correct burial of bodies and their search in mass graves. The current humanitarian crisis and the complexity of the context make it necessary to consider the overlaps between cases of the disappeared and unidentified bodies, between search and identification.

El hallazgo de fosas clandestinas se ha convertido en un hecho recurrente durante los últimos diez años en México, estimándose que podrían existir más de 2000 repartidas por todo el país (Guillen et al., 2018). Menos conocidas, reportadas y atendidas son las fosas comunes, localizadas en panteones municipales o estatales, que albergan cuerpos de personas no identificados y de las cuales no hay un censo oficial. Se estima que existen unos 26000 cuerpos en calidad de no identificados (SEGOB, 2019a) y anualmente, tan solo en la Ciudad de México, son destinados a la fosa común cementerial casi 500. Se requieren proyectos integrales en ciencia forense, que mitiguen el alto porcentaje de cuerpos sin identificar, que coordinen la correcta inhumación de cuerpos y su registro en fosas comunes. La crisis humanitaria vigente y la complejidad del contexto precisan considerar las imbricaciones entre casos de desaparecidos y cuerpos no identificados, entre búsqueda e identificación.
Cuerpos no identificados en el contexto Mexicano
Keywords: Forensic anthropology; unidentified; mass grave; Mexico; human rights